Key performance indicators of hospital supply chain: a systematic review - Meysam Fallahnezhad; Mostafa Langarizadeh; Afshin Vahabzadeh (BMC Health Services Research)
Abstract Background Performance measurement is vital for hospitals to become service-oriented, operate efficiently, attract customers, increase revenue, and improve both clinical and non-clinical outcomes, enabling them to succeed in the competitive healthcare sector. Key Performance Indicators (KPIs) play a crucial role in monitoring, assessing, and enhancing care quality and service delivery. However, identifying suitable KPIs for performance measurement can be challenging for hospitals due to a lack of comprehensive sources. Although many studies have explored KPIs, few have specifically addressed performance indicators within the hospital supply chain. Objectives This systematic review seeks to identify and categorize the current knowledge and evidence concerning KPIs for the hospital supply chain. Methods Seven bibliographic databases (PubMed, Scopus, Science Direct, Web of Science, Embase, ProQuest, and IEEE Xplore) were utilized in this research. The initial search identified 3661 articles; following a review of the titles, abstracts, and full texts, 32 articles were selected. Additionally, backward reference list checks were performed on the selected studies. Relevant studies were included based on the objectives, and data extraction was conducted using a form created in Word 2016. Results A total of 64 KPIs for the hospital supply chain were identified. The performance indicators were categorized into financial (n = 37), managerial (n = 15), and clinical (n = 12) categories. Conclusions This comprehensive review successfully identified 64 KPIs, highlighting their potential to advance clinical practice and enhance patient care in hospitals. Further research is essential to establish a standardized methodology for KPI development within the hospital supply chain.